Development of an adolescent alcohol misuse intervention based on the Prototype Willingness Model: A Delphi study. Issue 3 (4th April 2016) - Davies, Emma; Martin, Jilly; Foxcroft, David
Abstract : Purpose: – The purpose of this paper is to report on the use of the Delphi method to gain expert feedback on the identification of behaviour change techniques (BCTs) and development of a novel intervention to reduce adolescent alcohol misuse, based on the Prototype Willingness Model (PWM) of health risk behaviour. Design/methodology/approach: – Four BCTs based on the PWM were identified and incorporated into a draft intervention that aimed to change alcohol prototypes and enable adolescents to deal with social pressure. Using the Delphi process, successive questionnaires were distributed to 20 international experts to build consensus on the theoretical validity of the intervention. Findings: – In total, 15 experts completed round 1 and 11 completed round 2 of the Delphi study. A high level of consensus was achieved. Four priority areas were identified to improve the intervention: incorporating extra techniques to address social pressure; increasing intensity; providing incentives; and addressing credibility. Research limitations/implications: – The sample of experts was self-selected and four participants were lost between the first and second round of the study. Practical implications: – The effectiveness of the identified BCTs will be evaluated within an intervention to reduce alcohol misuse in adolescents. Further work should build towards a more unified approach to developing interventions based on the PWM. The Delphi method is likely to be particularly useful when there is no existing consensus about which BCTs to use that reflect certain theoretical constructs or that best target a specific population or behaviour. Originality/value: – This paper is the first to address the identification of specific BCTs based on the PWM and thus makes an important contribution to the application of this model to interventions. This novel application of the Delphi method also makes a useful addition to the growing field of intervention development and design.